Impact of Implementation Regulation of the Minister of Marine and Fisheries Number 56 and 57 of 2014 to the Fishing Industry in Bitung, North Sulawesi - Stanny S Rawung; Ficke H Rawung (Journal of International Conference Proceedings (JICP), 2018)
The fishing industry is the dominant driver of the economy in Bitung, it brings Bitung City known by the term "Skipjack". With the enactment of the Regulation of the Minister of Marine and Fisheries No 56 of 2014 on Temporary Cessation (Moratorium) Licensing of Fish in Regional Fisheries Management of the Republic of Indonesia and the Regulation of the Minister of Marine and Fisheries No. 57 of 2014 regarding the Second Amendment to the Regulation of the Minister of Marine and Fisheries No. 30 / MEN / 2012 on Business fisheries Regional fisheries Management in the Republic of Indonesia., brings a huge impact for the fisheries industry in Bitung.With the implementation of the regulation, not only affected the fishing industry, but also throughout the economy on the city of Bitungand North Sulawesi economy in general. This research will analyze the impact of the application of Regulation of the Minister of Marine and Fisheries No 56 and 57 2014. This study will examine the Fishing Industry Bitung city before and after implementation of the regulation. The study includes raw material supply chain, in this case the fish as the raw material for fishing industry are most severely affected by the regulation. Another issue will be discussed in this study are the multiplier effects caused by the application of the regulation. Keywords : Regulation of the Minister of Marine and Fisheries No 56 and 57 2014, the Fishing Industry Bitung, Supply Chain Management